Constituent materials micro-damage modeling in predicting progressive failure of braided fiber composites. (10th June 2016) - Nobeen, Nadeesh Singh; Zhong, Yucheng; Francis, Bernad A.P.; Ji, Xianbai; Chia, Elvin S.M.; Joshi, Sunil C.; Chen, Zhong
Abstract: Braided textile composite exhibits an efficient mechanism to distribute loads throughout its structure and have excellent impact resistant properties. Despite many works in the past, the successful prediction of braided textile composites strength still remains a challenge today. In this paper, a numerical simulation model based on a meso-scale approach is presented to predict the strength and damage behavior of braided textile composites. A meso-scale homogenized representative unit cell was built for the study using finite element analysis (FEA) method. 3D-Hashin and Stassi failure criteria were respectively selected for the yarn and the pure matrix, and coded in a subroutine in Abaqus finite element solver to study the individual constituents damages. From the different numerical studies, the failure mechanisms were observed to change with the braiding angle. The meso-scale computed results were also seen to agree closely with experimental and simulation results computed using a micro-mechanics failure approach.